Knowledge and Attitude of Staff Working in Healthcare Centers Regarding Childbearing - Raziyeh Rahmati; Talat Khadivzadeh; Habibollah Esmaily; HamidReza Bahrami (Mashhad University of Medical Sciences, 2019)
Background & aim: Knowledge and attitude of healthcare providers have an important role in the success of fertility-related programs. In this regard, the present study was conducted to determine the knowledge and attitude of midwives and family healthcare providers working in community health centers of Mashhad, Iran, regarding childbearing in 2015. Methods: This cross-sectional study was conducted on 108 health staff working at 18 health and treatment centers and 23 community health centers in Mashhad. The study population was selected by multi-stage random sampling technique. The data were collected by means of the childbearing knowledge and attitude questionnaires. Data analysis was performed in SPSS software (version 16) using descriptive statistics, as well as simple and multivariate correlation tests. Results: The mean scores of knowledge and attitude toward childbearing were obtained as 12.8±1.36 (out of 16) and 166.4±19.9 (out of 235) i.e at good and moderate levels, among the healthcare providers, respectively. The healthcare providers' knowledge about childbearing showed a significant relationship with age (P=0.001), duration of study (P=0.00), duration of marriage (P=0.00) and work experience (P=0.001). Attitude toward childbearing was also significantly associated with all mentioned variables (P Conclusion: Midwifery and family healthcare providers play a critical role in the enhancement of clients' knowledge and improvement of their attitude about childbearing. As their efforts would finally result in favorable changes in the rate of childbearing in the community. Thus, it is suggested to implement educational programs to enhance knowledge and attitude of healthcare providers to be able to promote childbearing in the society.